Mediating role of access to finance on the relationship between strategic orientation attributes and small medium enterprises (SMEs) performance in Nigeria - Ibrahim, Murtala Aminu; Mohd Shariff, Mohd Noor (2015)
In spite of recognized significant contribution of SMEs to the nation economy, Nigerian SMEs performance is below expectation.This is because SMEs in Nigeria today faces severe limitations in financing, management skill, marketing, modem technology and technical expertise. However, access to finance occupies a central position for the low performance of the SMEs in Nigeria. The objective of this study is to investigate the mediating role of access to finance on the positive relationship between entrepreneurial orientation (EO), market orientation (MO), learning orientation (LO), technology orientation (TO) and the performance of SMEs in Nigeria To achieve this objective a cross sectional survey was conducted.A sample size of 552 SMEs operating in Kano, Kaduna and Sokoto states of Nigeria were selected using stratified simple random sampling technique. Partial Least Squares Structural Equation Modelling was used to analyze the data.This study finds that EO, LO and TO are important strategic orientations for the performance of SMEs in Nigeria. The findings reveal that SMEs' access to finance depends on the degree of MO, LO and TO of the enterprise.It is expected EO would improve a firm's accessibility to finance, but the finding of this study does not support this expectation as EO negatively influences firm performance. Interestingly, the results further show that with better access to finance, MO, LO and TO influence firm performance.The results of path analysis indicate that access to finance mediates the positive relationship between MO, LO, TO and the performance of SMEs in Nigeria. This is important additional explanation for the existence of the relationship between these strategic orientations and firm performance. The results further suggest that SMEs need to use their strategic activities to improve their ability to obtain finances in order to perform well.Finally, recommendations for further research are also discussed.